THE ROLE OF IN DISCLOSING FIRM VALUE - Santoso, Aprih; Widowariti, Sri Yuni (Jurnal Ekonomi Manajemen, 2022)
This study aims to analyze: (1) the role of CSR in partially moderating the effect of GCG and profitability on firm value. (2) the partial influence of GCG and profitability on firm value. This population is all manufacturing companies on the Indonesia Stock Exchange for the period 2015-2021. The sampling technique in this study used purposive sampling with the criteria of manufacturing companies listed on the IDX for 2015-2021, with the number of shares owned by the company's management totaling more than 1% of all outstanding shares. Thus, 21 companies were obtained. The data was processed by multiple regression analysis using the help of the IBM SPSS Statistic 25. Â In addition, there is a CSR variable to determine the effect of moderation on the relationship between the independent variable and the dependent variable, using the absolute difference value equation model. To see the type of moderation, two equation models are used, so that the regression model equation becomes:The results showed that GCG and profitability had a positive and significant effect on firm value. The results of testing the moderating variable showed that CSR moderated the effect of GCG and profitability on firm value